On the concept and sign an insurance case - T I Sultonova (RUDN Journal of Law, 2014)
This paper deals with concept and features of the insured event. The author analyzes the existing legal framework on the issue, in particular the Civil Code of the Republic of Tajikistan, as well as the RT Law «On Insurance». It’s given the formulation of the term of the insurance case from legal, and from doctrinal sources. The author concludes that the insured event has, along with the category of insurance risk characteristics of randomness and probability. Probability of the insured event is the degree of probability of occurrence of events, it embodies. In view of the inherent insurance case signs of randomness and probability justified conclusion about the inadmissibility of his understanding of what happened as a kind of event.